Turning fans into lovers: Content strategy for brand’s social media pages to build stronger relationship - Gita Novia Riani; Gita Gayatri (Jurnal Manajemen dan Pemasaran Jasa, 2023)
Effective delivery of a brand message and format through digital platforms has been a key focus in marketing. Therefore, this study aims to analyze how brand post characteristics can significantly impact consumer engagement on social media using different formats and messages. It provides comprehensive insights into how consumer engagement can lay the foundation for developing stronger customer relationships. Quantitative methods using an online questionnaire are used to determine the real motivation from respondents towards the brand post characteristics and the perception of their relationship with the brand. The results show that content type is the strongest factor in influencing consumers to engage with a brand post on Instagram. Therefore, this study provides a better understanding of social media marketers to plan and implement their content strategy effectively.